2016
DOI: 10.1038/srep24683
|View full text |Cite
|
Sign up to set email alerts
|

Sight restoration after congenital blindness does not reinstate alpha oscillatory activity in humans

Abstract: Functional brain development is characterized by sensitive periods during which experience must be available to allow for the full development of neural circuits and associated behavior. Yet, only few neural markers of sensitive period plasticity in humans are known. Here we employed electroencephalographic recordings in a unique sample of twelve humans who had been blind from birth and regained sight through cataract surgery between four months and 16 years of age. Two additional control groups were tested: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 64 publications
6
35
0
Order By: Relevance
“…In the ongoing activity we observed a reduced alpha power in PAF of CDCs corresponding to the findings in the visual system of subjects with neonatal cataracts ( Bottari et al , 2016 ). The present study extends the previous result by demonstrating that the effect is also observed in the auditory domain and that it can be localized to a higher-order sensory area.…”
Section: Discussionsupporting
confidence: 79%
“…In the ongoing activity we observed a reduced alpha power in PAF of CDCs corresponding to the findings in the visual system of subjects with neonatal cataracts ( Bottari et al , 2016 ). The present study extends the previous result by demonstrating that the effect is also observed in the auditory domain and that it can be localized to a higher-order sensory area.…”
Section: Discussionsupporting
confidence: 79%
“…The P1 wave has been hypothesized to be functionally closely related to alpha oscillations by Freunberger et al (2008), who suggested that both alpha activity and the P1 wave might reflect activity connected to the inhibition of neural systems related to ''task-irrelevant brain areas or task-irrelevant stimulus categories'' (p. 2339). As discussed above, Bottari et al (2016Bottari et al ( , 2018 found evidence that alpha oscillatory activity is compromised in CC individuals, suggesting that the neural mechanisms regulating the excitatory-inhibitory balance might be compromised as a result of congenital visual deprivation. Such an imbalance might manifest itself not only as alpha oscillatory deficits, but additionally might underlie the generally reduced P1 amplitude.…”
Section: Discussionmentioning
confidence: 89%
“…On the one hand, a lack of pruning might spread the visual stimulus driven activity to a larger number of neurons contralateral to the visual field in which the stimuli were presented. On the other hand, Bottari et al (2016) reported that alpha oscillatory activity was significantly reduced in CC individuals compared to MC and DC individuals. Alpha activity has often been associated with the regulation of the excitatory/inhibitory balance of neural circuits and has been linked to inhibitory neural circuit activity (Jensen & Mazaheri, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In the context of indistinguishable CM thresholds in the SC and VM group, the present results suggest that the CM processing deficits of the CC individuals must be because of changes in the neural circuits associated with CM processing. In fact, a previous EEG study reported that α oscillations which have been associated with global motion processing ( Händel et al, 2007 ) were greatly reduced in CC individuals ( Bottari et al, 2016 ). It could be argued that the selective deficit in CM perception of CC individuals was predominantly because of the presence of nystagmus in this group.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, studies in individuals treated for congenital cataracts (CC) have revealed incomplete recovery in many visual functions, including visual acuity (VA; Ellemberg et al, 1999 ), stereovision ( Tytla et al, 1993 ), visual feature binding ( Putzar et al, 2007 ; McKyton et al, 2015 ), global motion processing ( Ellemberg et al, 2002 ; Bottari et al, 2018 ), and face processing ( Le Grand et al, 2001 ; Röder et al, 2013 ), while functions such as color discrimination ( Brenner et al, 1990 ; Pitchaimuthu et al, 2019 ) seemed to emerge independently of early visual experience. Biological motion (BM) processing, e.g., the ability to detect the movement of biological figures with sparse information ( Johansson, 1973 ), has been shown to recover well following early visual deprivation ( Hadad et al, 2012 ), that is, both detection thresholds as well as neural signatures have been observed to be indistinguishable between a CC group and normally sighted controls (SC group; Bottari et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%